Education and the significance of life - "Krishnamurti, J." (Chennai, 2005)
Krishnamurti had a life-long interest in education, and this book is the earliest and most expository of his books on the subject. Focusing on the central vision that life 'has a wider and deeper significance' and that it is the concern of education to come upon it, he explores various other connected themes - authority versus freedom, discipline, intelligence, and the role of religion in education.
Keywords: "Philosophy, Indic"